Freeman–Sheldon Syndrome: First Molecularly Confirmed Case from Sub-Saharan Africa - A. M. Ali; R. M. Mbwasi; G. Kinabo; E.-J. Kamsteeg; B. C. Hamel; M. C. J. Dekker (Case Reports in Genetics)
We report a case of a male baby who has characteristic signs of Freeman–Sheldon syndrome, a rare but recognizable, severe autosomal dominant form of distal arthrogryposis. Diagnosis was based on the distinctive clinical characteristics of the syndrome and confirmed by genetic analysis that showed a de novo missense mutation c.2015G>A (p.Arg672His) of the MYH3 gene. We highlight the different features present in our patient and describe the etiology of the Freeman–Sheldon phenotype and how its clinical complications can be dealt with. To the best of our knowledge, this is the first molecularly confirmed case of Freeman–Sheldon syndrome in sub-Saharan Africa.